Web Accessibility Evaluation Methods: A Systematic Review - Nuñez, Almendra (2019)
In this paper, we present the results of a systematic review involving the techniques or methods of web accessibility currently used, the domains that have been covered and the disabilities that were focused. The search strategy identified 343 studies, where only 20 were finally selected for the review. We found that automatic tools are the most frequent techniques used to evaluate web accessibility. In addition, most studies performed in the educational domain and the majority of studies do not focus on a special disability.